2010
DOI: 10.1038/nrcardio.2010.16
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of stress (Takotsubo) cardiomyopathy

Abstract: Stress cardiomyopathy, also referred to as Takotsubo cardiomyopathy, transient apical ballooning or broken heart syndrome, is a disorder associated with transient left ventricular dysfunction. Symptoms include acute chest pain and dyspnea accompanied by electrocardiographic changes, such as ST-segment elevation and T-wave inversions, minimal elevation of cardiac enzyme levels and transient wall-motion abnormalities in the absence of substantial coronary artery obstruction. Complete recovery of contractile func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
192
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(202 citation statements)
references
References 65 publications
2
192
1
3
Order By: Relevance
“…Several hypotheses have been presented to explain this unique cardiac disorder in TTC (15)(16)(17)(18)(19) and broadly divided into a vascular or myocardial cause. These may not be mutually exclusive because the entire cardiovascular system is exposed to the same catecholamine storm.…”
Section: Introductionmentioning
confidence: 99%
“…Several hypotheses have been presented to explain this unique cardiac disorder in TTC (15)(16)(17)(18)(19) and broadly divided into a vascular or myocardial cause. These may not be mutually exclusive because the entire cardiovascular system is exposed to the same catecholamine storm.…”
Section: Introductionmentioning
confidence: 99%
“…Once this area is affected there is loss of sympathetic inhibition leading to catecholamine surge in the body which can lead to myocytolysis [14]. This subsequent catecholamine surge may also induce LV dysfunction with LV apical ballooning [2][3][4]. Imaging showed that patient with raised troponin have stroke that more commonly involved the right posterior, superior, and medial insula and the right inferior parietal lobe exerting loss of inhibition of sympathetic pathway by insular cortex [13].…”
Section: Discussionmentioning
confidence: 99%
“…Literature search demonstrated that Electrocardiographic (ECG) changes might be seen with acute stroke. Various mechanisms have been set forth to validate the relation between acute stroke and troponin elevation with ECG changes which are imputed to the increase in catecholamine, which in turn, lead to myocyte injury [2][3][4] . Elevated troponin is seen after stroke and is associated with increased mortality [5].…”
Section: Introductionmentioning
confidence: 99%
“…We believe that catecholamine surge is an important condition for initial energy failure and could explain some pathological findings such as contraction band necrosis and interstitial edema (4). As long as the balance between energy demand and supply is maintained, catecholamine alone cannot account for the development of TCM.…”
Section: Catecholamine Cardiotoxicitymentioning
confidence: 99%
“…Many papers have reported enhanced catecholamine levels in TCM patients (3,4). We believe that catecholamine surge is an important condition for initial energy failure and could explain some pathological findings such as contraction band necrosis and interstitial edema (4).…”
Section: Catecholamine Cardiotoxicitymentioning
confidence: 99%